Inhibition of the AIF/CypA complex protects against intrinsic death pathways induced by oxidative stress - Doti, N (Nature Publishing Group, 2014)
Delayed neuronal cell death largely contributes to the progressive infarct development and associated functional impairments after cerebral ischemia or brain trauma. Previous studies exposed a key role for the interaction of the mitochondrial protein apoptosis-inducing factor (AIF) and cytosolic cyclophilin A (CypA) in pathways of programmed cell death in neurons in vitro and in vivo. These studies suggested that pro-apoptotic activities of AIF, such as its translocation to the nucleus and subsequent DNA degradation, depend on the physical interaction of AIF with CypA. Hence, this protein complex may represent a new pharmacological target for inhibiting the lethal action of AIF on the brain tissue. In this study, we show that the AIF amino-acid residues 370–394 mediate the protein complex formation of AIF with CypA. The synthetic AIF(370–394) peptide inhibited AIF/CypA complex formation in vitro by binding CypA with a K(D) of 12 μM. Further, the peptide exerted pronounced neuroprotective effects in a model of glutamate-induced oxidative stress in cultured HT-22 cells. In this model system of AIF-dependent cell death, the AIF(370–394) peptide preserved mitochondrial integrity, as detected by measurements of the mitochondrial membrane potential and quantification of mitochondrial fragmentation. Further, the AIF(370–394) peptide inhibited perinuclear accumulation of fragmented mitochondria, mitochondrial release of AIF to the nucleus and glutamate-induced cell death to a similar extent as CypA-siRNA. These data indicate that the targeting of the AIF-CypA axis is an effective strategy of neuroprotection.